Induction of Artificial Reproduction of Common Carp in Winter by Temperature Program in Conditions of Uzbekistan - Iroda Zokhidova (American Journal of Biology and Natural Sciences, 2025)
In December 2022, 4-year-old matured females and males of common carp (Cyprinus carpio) were placed in the RAS and the control group in an earthen pond. In the RAS and in the pond, the water was 14-15 °C. Since the beginning of January, the water temperature in the RAS began to increase by 1°C every two days. In early February, the fish from the RAS and from the ponds were injected by pituitary injections according to routine method of artificial reproduction. The fish from the RAS gave mature eggs and sperm, and the eggs were successfully incubated. The fish from the ponds did not respond to the injections, their gonads remained at stage III – IV.